Developing techno-economically sustainable methodologies for deep desulfurization using hydrodynamic cavitation - Suryawanshi, N.B. (Fuel, 2017)
The present work, for the first time, describes the efficacy of the cavitation process and compares the cavitation yield for two types of cavitation devices-one employing linear flow for the generation of cavities and other employing vortex flow. The process involves pre-programmed mixing of the organic and aqueous phases, and can be carried out using simple mechanical cavitating devices such as orifice or vortex diode. The process essentially exploits in situ generation of oxidising agents such as hydroxyl radicals for oxidative removal of sulfur. The efficiency of the process is strongly dependent on the nature of device apart from the nature of the organic phase. The effects of process parameters and engineering designs were established for three organic solvents (n-octane, toluene, n-octanol) for model sulfur compound-Thiophene. A very high removal to the extent of 95% was demonstrated. The results were also verified using commercial diesel. The cavitation yield is significantly higher for vortex diode compared to the orifice. The process has potential to provide a green approach for desulfurization of fuels or organics without the use of catalyst or external chemicals/reagents apart from newer engineering configurations for effective implementation of hydrodynamic cavitation in industrial practice and also appears to be economically sustainable.
Keywords: Fuel; Oxidation; Petroleum; Pollution Control; Sulphur Removal

Solvent-assisted cavitation for enhanced removal of organic pollutants - degradation of 4-aminophenol - Patil, Pravin B.; Bhandari, Vinay M. (Journal of Environmental Management, 2022)
A new approach of solvent-assisted cavitation process was proposed for degradation of organic pollutants. The process envisages the use of suitable solvent as an additive, (1-5% v/V), in the conventional cavitation process to enhance the pollutant removal efficiency. A proof of concept was provided for the removal of ammoniacal nitrogen with significantly improved efficiency using solvent-assisted hydrodynamic cavitation (HC) compared to conventional HC. The efficacy of the process was studied on a pilot plant scale (1 m(3)/h) and using vortex flow based vortex diode as a cavitating device. Degradation studies were carried out using a model pollutant, 4-amino phenol and four different solvents as additives, 1-octanol, cyclohexanol, 1-octane and toluene. Relatively polar solvents were found to increase the efficiency of the pollutant removal (> 65%) and also increase the rates to an extent of more than 200%, compared to only HC. A very high removal of ammoniacal nitrogen, more than 90%, was obtained for solvents 1-octanol and cyclohexanol, indicating the importance of the selection of solvent. Per pass degradation model showed 3 to 4 times increase in the per pass degradation for polar solvents compared to cavitation alone. The results confirm no role of conventional solvent extraction and no specific contamination of wastewater due to the use of solvent as an additive in the process. Further, the cost was 2-3 times lower as compared to the conventional HC. The interesting observations in the proposed process can fuel further research to provide possible improvements in existing methodologies of wastewater treatment, in general, and for removal of ammoniacal nitrogen, in particular.
Keywords: Ammoniacal nitrogen; Hydrodynamic cavitation; Oxidation; Pollution Control; Wastewater treatment